Hubungan Pola Asuh Otoriter dengan Agresivitas Mahasiswa dalam Hubungan Berpacaran - Natasya Caesarico Adrecy (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This research was designed to: 1) determine the relationship between authoritarian parenting styles and students' aggressiveness in dating relationships, 2) describe the level of intensity of authoritarian parenting patterns experienced by students, 3) describe the level of aggressiveness in dating relationships carried out by students. Data was collected using a questionnaire method with purposive sampling technique. The criteria for respondents needed in this research are students who have experienced authoritarian parenting and are currently in a dating relationship. Through correlational hypothesis testing, the pearson correlation was obtained at a value of 0.722 with a significance of 0.00 < 0.05.The results of this research show that: 1) there is a relationship between authoritarian parenting style and aggressiveness in dating students, 2) the results of achieving the level of authoritarian parenting experienced by students are in the high category, 3) the results of achieving the level of aggressiveness in dating students are in the low category.